2017
DOI: 10.3389/fphar.2017.00454
|View full text |Cite
|
Sign up to set email alerts
|

In Metastatic Non-small cell Lung Cancer Platinum-Based Treated Patients, Herbal Treatment Improves the Quality of Life. A Prospective Randomized Controlled Clinical Trial

Abstract: Background: According to clinical experience, Traditional Chinese Medicine (TCM) herbs added to platinum-based therapy (PBT) improve the Quality of Life (QOL) in metastatic non-small cell lung cancer (NSCLC) patients, but this must be prospectively validated.Patients and Methods: Based on clinical impressions regarding the effect of adding TCM herbs to platinum-based chemotherapy, we anticipated that 2 × 21 patients would be sufficient to obtain significant results with an α < 0.05 and power (1 - β) of 90%. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…The use of traditional Chinese medicine (TCM) in the treatment of diseases has a long history in China 11 13 . Compared with Western medicine, TCM provides another effective treatment option with relatively mild side effects 14 16 . In recent years, relevant studies on the use of TCM in cancer treatment have gradually attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…The use of traditional Chinese medicine (TCM) in the treatment of diseases has a long history in China 11 13 . Compared with Western medicine, TCM provides another effective treatment option with relatively mild side effects 14 16 . In recent years, relevant studies on the use of TCM in cancer treatment have gradually attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…Developed by the Rush-Presbyterian-St. Luke Medical Center in Chicago, the scale is the most widely used scale for evaluating the quality of life of NSCLC patients in the past 20 years. 16,17 The FACT-L version 4.0 used in this study is a Chinese version equivalent to 2000 Chinese finished by Wan Chonghua. It includes a common module consisting of a total of 34 items (physical status (8), social/ family status (8), relationship with doctors (3), emotional status (7), and functional status (8)) (i.e.…”
Section: Functional Assessment Of Cancer Treatment-lung Fact-l 40mentioning
confidence: 99%
“…It has been proved that the adjuvant treatment of TCM is effective in improving the overall survival rate among lung cancer patients [5] . TCM is capable to enhance host immune response, reduce the adverse reactions of chemotherapy [6] , and improve the quality of life for patients [7] . A study to investigated the frequencies and patterns of TCM herbal treatment for lung cancer patients in Taiwan found that Platycodon grandi orum and Mai-Men-Dong-Tang (MMDT) were important TCM herbs by network analysis [8] , which suggests that, Platycodon grandi orum plays a signi cant role in the treatment of lung cancer patients [9] .…”
Section: Introductionmentioning
confidence: 99%